Influence of spectral characteristics inherent to cameras on color rendering in multimedia images - Pyliavskyi, V.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2021)
The paper presents the research results concerning the end devices of multimedia paths. It is focused on the spectral characteristics of human vision, which are basic for the creation of light-to-signal converters. The influence of changes in the spectral characteristics of the sensitivity of the converters on the color rendition in the end-to-end multimedia path has been investigated. Changes in the spectral characteristics of the transducers caused by the refined spectral characteristics of CIE06 vision, supplemented with previously unknown characteristics of vision (ipRGC model), as well as one of the possible variants of color perception impairment (data of Prof. M. Neitz), have been considered. An algorithm has been presented, which allows calculating the spectral characteristics for new and promising light-to-signal converters, depending on the spectral characteristics of vision properties. Analytical expressions have been proposed, which make it possible to correct the color signals of the existing light-to-signal converters to ensure the required level of color rendering quality in the end-to-end path. Estimates of the effectiveness of the proposed algorithm have been given. У статті представлено результати досліджень кінцевих пристроїв мультимедійних шляхів. Основну увагу приділено спектральним характеристикам людського зору, які є основними для розробки перетворювачів світло-сигнал. Досліджено вплив змін спектральних характеристик чутливості перетворювачів на передавання кольору в наскрізному мультимедійному тракті. Зміни спектральних характеристик перетворювачів через уточнені спектральні характеристики зору CIE06 доповнено раніше невідомими характеристиками зору (модель ipRGC), а також одним із можливих варіантів порушення сприйняття кольору (дані проф. М. Нейца). Наведено алгоритм, який дозволяє обчислювати спектральні характеристики для нових і перспективних перетворювачів залежно від спектральних властивостей зору. Запропоновано аналітичні вирази, які дають можливість коригувати кольорові сигнали існуючих перетворювачів, щоб забезпечити необхідний рівень якості передачі кольорів у наскрізному шляху. Наведено оцінки ефективності запропонованого алгоритму.